On the amount and timing of project payments with hints to customary contracting in Germany - Alf Kimms (Gestão & Produção, 2007)
A huge number of publications deal with project scheduling and very often the objective is to minimize the makespan. We claim that in the real world money counts. Therefore, we review how project payments can be defined in practice. The issues of contracting and bidding are discussed to demonstrate that a whole universe of specific model formulations would be needed to cover real situations.